Block backward differentiation formulas with automatic order selection for solving ordinary differential equations - Ibrahim, Zarina Bibi; M. Nasir, N. A. A.; Othman, Khairil Iskandar; Suleiman, Mohamed (2014)
In this paper, a class of Block Backward Differentiation Formulas (BBDFs) are developed using fixed step size with automatic order selection for the numerical solution of stiff ordinary differential equations (ODEs). The method is derived by combining the BBDF methods of order four, five and six as single code with strategy on order selection. The proposed BBDF is validated through numerical results on some standard problems found in the literature and comparisons are made with single order BBDF. Numerical results shows the advantage of using BBDF with automatic order selection for solving ODEs.